Etwas für alle – Ausgewählte Texte von und mit Abraham a Sancta Clara digital - Claudia Resch (Zeitschrift für digitale Geisteswissenschaften)
This paper aims to introduce a new web-based digital edition of printed German texts written by or ascribed to Abraham a Sancta Clara, who was a renowned Augustinian monk and a widely read author at his time. The texts are part of the thematic memento mori research collection, Austrian Baroque Corpus, now freely available through the Austrian Centre for Digital Humanities: https://acdh.oeaw.ac.at/abacus/ One of the main considerations of the paper was how to shape the annotation process in a way that would meet the needs of linguistic, literary and cultural studies. This objective necessitated a user-friendly visualization that would be suitable to the research questions of a broader audience.